A Role of DLPFC in the Learning Process of Human Mate Copying - Zhuang, Jin-Ying; Xie, Jiajia; Hu, Die; Fan, Mingxia; Zheng, Li (Frontiers in Psychology, 2016)
In the current study, we conducted a behavioral experiment to test the mate coping effect and a functional magnetic resonance imaging (fMRI) experiment to test the neural basis involved in the social learning process of mate copying. In the behavioral experiment, participants were asked to rate the attractiveness of isolated opposite-sex (potential mates) facial photographs, then shown the targets associating with a neutral-faced model with textual cues indicating the models’ attitude (interested vs. not-interested) towards the potential mates, and then asked to re-evaluate the potential mates’ attractiveness. Using a similar procedure as the behavioral experiment, participants were scanned while observing the compound images in the fMRI experiment. The mate copying effect was confirmed in the behavioral experiment –greater increase in attractiveness ratings was observed for opposite-sex photographs in the interested than in the not-interested condition. The fMRI results showed that the dorsolateral prefrontal gyrus (DLPFC) was significantly active in the comparison of interested  not-interested condition, suggesting that a cognitive integration and selection function may be involved when participants process information from conditions related to mate copying.